2023
DOI: 10.48550/arxiv.2302.01986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of atomic disorder in Ni-V alloys

Abstract: We present a pair distribution function (PDF) analysis from neutron diffraction data of the Ni1−xVx alloy in the Ni-rich regime. Such structural study aims to clarify the origin of the magnetic inhomogeneities associated with the quantum Griffiths phase close to the ferromagneticparamagnetic quantum phase transition. The PDF analysis successfully reveals the details of the structure and chemical distribution of our Ni1−xVx polycrystalline samples prepared with hightemperature annealing and rapid cooling protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, detailed studies around the quantum critical region are lacking. It is interesting to note that Gebretsadik et al [48] have reported the presence of residual strain in the crystal structure of Ni 1−x V x near the qcp as obtained from neutron diffraction data based on pair distribution function analysis but the local structure was found to be same as in the case of pure Ni.…”
Section: Introductionmentioning
confidence: 89%
“…However, detailed studies around the quantum critical region are lacking. It is interesting to note that Gebretsadik et al [48] have reported the presence of residual strain in the crystal structure of Ni 1−x V x near the qcp as obtained from neutron diffraction data based on pair distribution function analysis but the local structure was found to be same as in the case of pure Ni.…”
Section: Introductionmentioning
confidence: 89%